The politics of global supply chains : power and governance beyond the state - Macdonald, Kate, 1976- (Malden, MA : Polity, 2014)
This is the first book to deal with'supply chain politics' a phrase that is becoming increasingly commonplace. The book focuses primarily on coffee and garment supply chains, using these as case studies, showing how the political struggles within them both reflect and fuel the on-going re-shaping of global governance.
Introduction: The politics of global supply chains -- 1. Power and governance in garment supply chains -- 2. The emergence of non-state governance: Anti-sweatshop campaigns -- 3. The private sector response: Codes of conduct -- 4. Dispersed power Wwthin coffee supply chains -- 5. The transformative challenge: Fair trade as an'alternative' institutional model -- 6. Starbucks CAF{u2160}practices: The'responsible' corporation responds -- 7. Interaction between initiatives: Diffusing change beyond'niche' supply chains -- 8. Lessons and synthesis: Power, responsibility and governance beyond the state -- Conclusion: Ongoing political contests in global supply chains.
Includes bibliographical references (pages 222-244) and index.
Keywords: Business logistics -- Political aspects; Corporate governance; Strategic planning; Coffee industry; Clothing trade